C05 The role of FAN1 nuclease activity and mlh1 binding in stabilisation of the cag repeat in HD-IPSC derived models. (12th September 2022) - Donaldson, Jasmine; Hamilton, Joseph; Olive, Jessica; Goold, Robert; Tabrizi, Sarah J
Abstract : Background: Huntington's disease (HD) is caused by an expanded trinucleotide CAG repeat in the huntingtin gene, HTT. Ongoing expansion of the CAG tract in affected tissues, known as somatic expansion, correlates with an earlier age at onset and faster disease progression. DNA damage response proteins drive somatic expansion, and MSH2, MSH3 and MLH1 are all required for expansions to occur. FAN1, a nuclease involved in DNA interstrand cross-link repair, is the strongest disease modifier for Huntington's Disease (HD) onset and plays an important role in protecting against somatic expansions. FAN1 does so via its nuclease activity which likely promotes accurate repair at the CAG repeat, but may have another distinct function conferring protection. We recently identified a highly conserved SPYF motif at the N terminus of FAN1 that binds to MLH1. This interaction prevents the recruitment of MLH1 by MSH3, thereby reducing somatic expansion. Promoting the FAN1-MLH1 complex interaction therefore represents an unexplored therapeutic strategy. Methods: We have utilised CRISPR-Cas9 to knock out FAN1 and introduce mutations ablating FAN1 nuclease activity (D960A) and/or disrupting the SPYF motif (Y128A/F129A) in an induced pluripotent stem cell (iPSC) model with 125 CAG repeats. Results: FAN1 knock-out clones retain pluripotency and show increased sensitivity to crosslinking agent mitomycin C. Loss of FAN1 potentiates somatic expansion in iPSCs and iPSC-derived neurons. We are currently exploring the effect of the D960A and Y128A/F129A mutations on repeat expansions in iPSC-derived neurons. Conclusions: These data will highlight potential avenues for HD therapeutics in attenuating somatic expansion.